Perceptions of quality across the maternal care continuum in the context of a health financing intervention: Evidence from a mixed methods study in rural Malawi - Kambala, Christabel; Lohmann, Julia; Mazalale, Jacob; Brenner, Stephan; Sarker, Malabika; Muula, Adamson Sinjani; De Allegri, Manuela (© 2017 BioMed Central Ltd., 2018)
This article was published in the BMC Health Services Research [© 2017 BioMed Central Ltd.] and the definitive version is available at: http://doi.org/10.1186/s12913-017-2329-6 The Journal's website is at: https://bmchealthservres.biomedcentral.com/articles/10.1186/s12913-017-2329-6